A sociological reinterpretation of hadith on grave visitation - Dadah Dadah; Haziq Hafizuddin Lubis (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
The increasing polarization between normative textual interpretations and lived religious practices in contemporary Muslim societies underscores the urgent need for integrative analytical approaches that bridge doctrine and social reality. This study offers a novel sociological reinterpretation of hadith on grave visitation by examining its transformation from a normative legal discourse into a dynamic and institutionalized social practice. Employing a qualitative library-based design within the frameworks of the Sociology of Hadith and Living Hadith, the study analyzes canonical hadith texts, classical commentaries, and contemporary scholarly literature. The findings demonstrate that the shift from prohibition to recommendation of grave visitation reflects a deliberate form of prophetic social engineering aimed at restructuring emotional behavior and redefining collective attitudes toward death. Furthermore, the study reveals that hadith establishes a system of theological and spatial regulation that preserves monotheistic boundaries while enabling controlled engagement with burial spaces. Grave visitation is reinterpreted as an existential practice that fosters internalized moral awareness and ethical self-regulation. In contemporary contexts, particularly in Indonesia, the practice evolves into a Living Hadith manifested in communal rituals that reinforce social cohesion, collective memory, and cultural continuity, while also revealing tensions arising from the interaction between textual authority and local cultural dynamics. This study advances the theoretical development of the Sociology of Hadith by conceptualizing hadith as a mechanism of internalized social regulation and moral governance. Ultimately, it positions grave visitation as a multidimensional and socially embedded institution, offering a new conceptual lens for understanding the role of prophetic traditions in shaping religious practice within the global discourse on religion and society.